1982
DOI: 10.1021/bi00258a015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lipids on acetylcholine receptor. Essential need of cholesterol for maintenance of agonist-induced state transitions in lipid vesicles

Abstract: The effects of lipids on the maintenance of characteristic functional properties of the acetylcholine receptor during the course of reconstitution into lipid vesicles were studied by following the kinetics of agonist-induced state transitions. The requirements for successful preservation of these properties could be dissected into two components: (a) adequate nature and concentration of lipids during detergent solubilization; (b) correct lipid environment during reincorporation into lipid vesicles by the chola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(126 citation statements)
references
References 64 publications
4
122
0
Order By: Relevance
“…Forty large cell profiles (with a total of 2990 and 4812 golds, respectively) were included in the quantification from each experiment. a Data and calculations based on Hansen et al, 1992. TION, cholesterol is important for the structure and function of membrane proteins (Muller and Shinitzky, 1979;Criado et al, 1982;Bloch, 1991;Kilsdonk et al, 1995), and furthermore, a change in the cholesterol content will affect the membrane viscosity, the exposure of membrane proteins to the surroundings, and therefore also the interaction between membrane proteins and cytosolic proteins (Shinitzky and Inbar, 1974;Shinitzky and Rivnay, 1977). Such changes might be responsible for the inhibition of formation of clathrincoated pits observed here.…”
Section: Role Of Cholesterol In Endocytosismentioning
confidence: 88%
See 1 more Smart Citation
“…Forty large cell profiles (with a total of 2990 and 4812 golds, respectively) were included in the quantification from each experiment. a Data and calculations based on Hansen et al, 1992. TION, cholesterol is important for the structure and function of membrane proteins (Muller and Shinitzky, 1979;Criado et al, 1982;Bloch, 1991;Kilsdonk et al, 1995), and furthermore, a change in the cholesterol content will affect the membrane viscosity, the exposure of membrane proteins to the surroundings, and therefore also the interaction between membrane proteins and cytosolic proteins (Shinitzky and Inbar, 1974;Shinitzky and Rivnay, 1977). Such changes might be responsible for the inhibition of formation of clathrincoated pits observed here.…”
Section: Role Of Cholesterol In Endocytosismentioning
confidence: 88%
“…A major fraction of cholesterol is present in the plasma membrane (Lange, 1991), and cholesterol is important for various processes at the cell surface. For instance, there seems to be a direct interaction between the oxytocin receptor and cholesterol (Klein et al, 1995), and also the acetylcholine receptor was found to have a functional requirement for cholesterol (Criado et al, 1982). Furthermore, it has been proposed that annexin II, which is involved in the endocytic pathway (Creutz, 1992;Gruenberg and Emans, 1993), serves as an interface between membranes containing a high amount of cholesterol and the actin cytoskeleton (Harder et al, 1997), and it is clear that cholesterol is essential for the structure and function of invaginated caveolae, including the caveolae-dependent endocytosis that has been reported in some cell types (Rothberg et al, 1990;Parton et al, 1994;Parton, 1996;Smaby et al, 1996;Chang et al, 1998;Hailstones et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation for this discrepancy could be the lipid composition of the membranes surrounding the receptor molecules. It has been well established that the lipid composition, especially the cholesterol concentration, is important for the activity, of some membrane-bound hormone receptors such as the nicotinic acetylcholine receptor and the p2 adrenergic receptor (Criado et al, 1982; Kirilovski and Schramm, 1982). In fact, the affinity of the transferrin receptor for its ligand can be modulated by changing the cholesterol contents of the sourrounding lipid bilayer (Nunez and Glass, 1982).…”
Section: Cellular Localization Of the D Receptor Heterologously Promentioning
confidence: 99%
“…As described in the Introduction, the functionality of the AChR (both the passage of ions across the pore and the transition from the R to the D states of the receptor) is highly sensitive to the composition of the surrounding lipid. Speculative models on the role of membrane fluidity on AChR function have been proposed (55,56). Baenziger and co-workers suggest that membrane fluidity modulates the relative proportion of AChR in the R and D states (45).…”
Section: Discussionmentioning
confidence: 99%